UNKNOWN IVAN ZOUBENCO: STROKES TO CREATIVE BIOGRAPHY - Kasyanenko, T. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
After having collected archival material, the author of the article reveals features of vital and creative biography of yet unknown for public figure of the writer, cultural and civic leader Ivan Zubenko (1888-1940). Research reveals a new perspective not only on literary and artistic feature of the Western Ukrainian cultural process of past period, but also on psychological aspects of creativity, motivation of appearance of lyrical, epic and dramatic works of Ivan Zubenko.